EFEKTIVITAS MEDIA GAMBAR DALAM PENGAJARAN KUREMASU PADA MATA KULIAH STRUKTUR (BUNPOO) BAHASA JEPANG - Diner, Lispridona (Universitas Negeri Semarang, 2009)
The research was aimed to know the effectiveness of picture as media inteaching kuremasu in Japanese Structure class. The research is quantitative. The datawere the students’ ability after attending kuremasu presented through picture. Themethod of the research is experimental. The data were analyzed with t-test. The resultshowed that most of the students’ ability improved after having the picture as a mediain teaching kuremasu.Kata kunci : kuremasu, media gambar